The religions book : [big ideas simply explained] - Ambalu, Shulamit; Coogan, Michael David; Feinstein, Eve Levavi; Freedman, Paul; Philip, Neil; Stobart, Andrew; Thompson, Mel, 1946-; Tieszen, Charles Lowell, 1978-; Weeks, Marcus (New York : DK Publishing, 2013)
Religion has influenced human culture since prehistory, shaping everything from the politics of war and peace to notions of morality and issues of sex, reproduction, and family. On an individual level, it has also offered people a sense of meaning, purpose, and comfort, and even today, when science appears to offer answers to many of the worlds's conundrums, faith persists and many religions--including Christianity and Islam--are still growing. The Religions Book explains in a clear, accessible way more than 100 of the most important theological ideas, from those bound up in the earliest cultures to others that have emerged in the last few hundred years, along with all of the main tenets of the world's major faiths. In doing so, it considers key issues such as the problem of defining good and evil, the significance of suffering, creation and the afterlife ("Why are we here?" and "Why do we die?"), and the nature of god.--Publisher's description.
Primal beliefs from prehistory -- Ancient and classical beliefs from 3000 BCE -- Hinduism from 1700 BCE -- Buddhism from 6th century BCE -- Judaism from 2000 BCE -- Christianity from 1st century CE -- Islam from 610 CE -- Modern religions from 15th century.
Includes index.
Subtitle from cover.
Keywords: Religion; Religions